Hysteresis-free perovskite solar cells made of potassium-doped organometal halide perovskite - Tang, Zeguo; Bessho, Takeru; Awai, Fumiyasu; Kinoshita, Takumi; Maitani, Masato M.; Jono, Ryota; Murakami, Takurou N.; Wang, Haibin; Kubo, Takaya; Uchida, Satoshi; Segawa, Hiroshi (Scientific reports, 2017)
Potassium-doped organometal halide perovskite solar cells (PSCs) of more than 20% power conversion efficiency (PCE) without I-V hysteresis were constructed. The crystal lattice of the organometal halide perovskite was expanded with increasing of the potassium ratio, where both absorption and photoluminescence spectra shifted to the longer wavelength, suggesting that the optical band gap decreased. In the case of the perovskite with the 5% K + , the conduction band minimum (CBM) became similar to the CBM level of the TiO 2 -Li. In this situation, the electron transfer barrier at the interface between TiO 2 -Li and the perovskite was minimised. In fact, the transient current rise at the maximum power voltages of PSCs with 5% K + was faster than that without K + . It is concluded that stagnation-less carrier transportation could minimise the I-V hysteresis of PSCs.